Declining tibial curvature parallels ∼6150 years of decreasing mobility in central european agriculturalists. Issue 2 (11th February 2015) - Macintosh, Alison A.; Davies, Thomas G.; Pinhasi, Ron; Stock, Jay T.
ABSTRACT Long bones respond to mechanical loading through functional adaptation in a suite of morphological characteristics that together ensure structural competence to in vivo loading. As such, adult bone structure is often used to make inferences about past behavior from archaeological remains. However, such biomechanical approaches often investigate change in just one aspect of morphology, typically cross‐sectional morphology or trabecular structure. The relationship between longitudinal bone curvature and mobility patterns is less well understood, particularly in the tibia, and it is unknown how tibial curvature and diaphyseal cross‐sectional geometry interact to meet the structural requirements of loading. This study examines tibial curvature and its relationship with diaphyseal cross‐sectional geometry (CSG) and body size in preindustrial Central Europeans spanning ∼6150 years following the introduction of agriculture in the region. Anteroposterior centroid displacement from the proximo‐distal longitudinal axis was quantified at nine diaphyseal section locations (collectively representative of diaphyseal curvature) in 216 tibial three‐dimensional laser scans. Results documented significant and corresponding temporal declines in midshaft centroid displacement and CSG properties. Significant correlations were found between mid‐diaphyseal centroid displacement and all mobility‐related CSG properties, while the relationship weakened toward the diaphyseal ends. No significant relationship was found between centroid displacement and body size variables with the exception of the most distal section location. Results support a relationship between tibial curvature and cross‐sectional geometry among prehistoric Central European agricultural populations, and suggest that changes in mechanical loading may have influenced a suite of morphological features related to bone adaptation in the lower limb. Am J Phys Anthropol 157:260–275, 2015. © 2015 Wiley Periodicals, Inc.